Low-reflection member and coating liquid for low-reflection film
By using hollow particles and binder in low-reflection films and combining high boiling point solvents, the problem of insufficient wear resistance of existing low-reflection films is solved, and high wear resistance and low refractive index are achieved in the external environment Effect.
Patent Information
- Application Number
- CN202380044104.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-01
- Filing Date
- 2023-05-19
- Publication Date
- 2025-01-10
AI Technical Summary
The existing low-reflection films are not well-resistant when used in external environments, making it difficult to meet the requirements of outdoor use.
A low reflective film composed of hollow particles and binder is used to adjust the mass ratio and structure of hollow particles and binder, and combined with the use of a high boiling point solvent, a coating liquid with low refractive index and high wear resistance is formed. Apply to glass plates to ensure the stability and durability of the film.
The wear resistance performance of the low-reflective film is improved, and it can remain stable under high load conditions, with small changes in dynamic friction coefficient, extending the service life of the film.
Smart Images

Figure CN119301080A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a coating liquid for a low-reflection member and a low-reflection film. Background Art
[0002] Glass plates for displays of personal computers, smartphones, etc. have a problem of reduced visibility due to reflection of external light such as indoor lights and sunlight. In order to solve this problem, a method of forming a low-reflection film on the display has been developed (Patent Document 1).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2020-118992 Summary of the invention
[0006] Technical problem to be solved by the invention
[0007] Glass plates with such low-reflection films are sometimes used outdoors, and therefore have been required to have wear resistance in recent years. The present invention is made to solve this problem, and its purpose is to provide a low-reflection member and a coating liquid for a low-reflection film having wear resistance.
[0008] Technical solutions for solving technical problems
[0009] Item 1. A low-reflection component comprising:
[0010] A glass plate having a first surface and a second surface, and
[0011] a low reflection film formed on the first surface and having a refractive index lower than that of the glass plate,
[0012] The low-reflection film comprises hollow fine particles and a binder.
[0013] Even after a cotton swab was pressed against the low-reflection film with a load of 10 g or more and scraped once at a distance of 3 cm, the low-reflection film was not peeled off.
[0014] Item 2. A low-reflection component comprising:
[0015] A glass plate having a first surface and a second surface, and
[0016] a low reflection film formed on the first surface and having a refractive index lower than that of the glass plate,
[0017] The low-reflection film comprises hollow fine particles and a binder.
[0018] When the woven fabric was pressed against the low-reflection film with a load of 100 g and moved back and forth 10 times at a distance of 3 cm, the change in the dynamic friction coefficient between the first and tenth reciprocating movements was 0.2 or less.
[0019] Item 3. The low-reflection member according to Item 1 or 2, wherein in the low-reflection film, a mass ratio of the hollow fine particles to the binder is 50:50 to 99:1.
[0020] Item 4. The low-reflection member according to Item 1 or 2, wherein in the low-reflection film, a mass ratio of the hollow fine particles to the binder is 75:25 to 95:5.
[0021] Item 5. The low-reflection member according to any one of Items 1 to 4, wherein the binder contains silicon dioxide and polysilsesquioxane.
[0022] Item 6. The low-reflection member according to any one of Items 1 to 5, which has a refractive index of less than 1.20.
[0023] Item 7. The low-reflection member according to any one of Items 1 to 5, which has a refractive index of 1.18 or less.
[0024] Item 8. The low-reflection member according to any one of Items 1 to 7, wherein gaps are formed between the hollow fine particles, and the gaps have a diameter of 1000 nm. 2 The cross-sectional area above.
[0025] Item 9. The low-reflection member according to any one of Items 1 to 8, wherein the adhesive further comprises pores having a diameter of 700 nm. 2 The following cross-sectional area.
[0026] Item 10. A low-reflection member as described in any one of Items 1 to 9, wherein the low-reflection film does not peel off even after a cotton swab is pressed against the low-reflection film with a load of 50 g or more and scraped once at a distance of 3 cm.
[0027] Item 11. A low-reflection member as described in any one of Items 1 to 9, wherein the low-reflection film does not peel off even after a cotton swab is pressed against the low-reflection film with a load of 100 g or more and scraped once at a distance of 3 cm.
[0028] Item 12. The low-reflection member according to any one of Items 1 to 11, which has a pencil hardness higher than 2B.
[0029] Item 13. The low-reflection member according to any one of Items 1 to 12, which can be used as an optical component that can be housed inside a housing.
[0030] Item 14. The low-reflection structure as described in Item 13, wherein the optical component is a lens.
[0031] Item 15. The low-reflection member according to Item 13, wherein the optical component is a covering member, and the low-reflection film is configured to face the inside of the frame.
[0032] Item 16. A coating liquid for a low-reflection film that can be applied on a glass plate, comprising: hollow fine particles, a binder, and a solvent having a boiling point of 200° C. or higher.
[0033] Effects of the Invention
[0034] According to the present invention, a low-reflection member having wear resistance can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a cross-sectional view showing one embodiment of the low-reflection member of the present invention.
[0036] Figure 2 for Figure 1 Enlarged cross-sectional view of .
[0037] Figure 3 A diagram showing a jig used for a durability test.
[0038] Figure 4 This is a SEM photograph showing a cross-sectional view of Example 1.
[0039] Figure 5 This is a SEM photograph showing a cross-sectional view of a comparative example.
[0040] Figure 6 This is a SEM photograph showing a cross-sectional view of Example 2.
[0041] Figure 7 It is a graph showing the change of the dynamic friction coefficient of Examples 1 and 2 and the comparative example.
[0042] Figure 8 The following are SEM photographs showing the surface of the comparative example before and after the test for measuring the change in the dynamic friction coefficient. DETAILED DESCRIPTION
[0043] Hereinafter, an embodiment of the low-reflection member of the present invention will be described with reference to the accompanying drawings. The low-reflection member of this embodiment can be used as a display of a personal computer, a mobile PC, a tablet PC, a smart phone, etc.; a cover member of the above display; an optical filter; and an optical component that can be housed in a frame (e.g., a lens, a cover member covering the lens). In addition, it can also be used in an optical component of a vehicle-mounted camera, a vehicle-mounted sensor, or a surveillance camera.
[0044] Figure 1 : is a cross-sectional view of a low-reflection member. As shown in the figure, the low-reflection member 100 of the present embodiment comprises: a glass plate 1 having a first surface 11 and a second surface 12; and a low-reflection film 2 laminated on the first surface 11 of the glass plate 1. The low-reflection member 100 is arranged to cover the protected member 200 such as the above-mentioned display. At this time, the second surface 12 of the glass plate 1 is arranged to face the protected member 200, and the low-reflection film 2 is arranged to face the outside. The following is a detailed description.
[0045] <1. Glass plate>
[0046] The glass plate 1 can be formed by other glasses such as general-purpose soda-lime glass, borosilicate glass, aluminosilicate glass, and alkali-free glass. In addition, the glass plate 1 can be formed by a float glass process. By this method, a glass plate 1 having a smooth surface can be obtained. However, the glass plate 1 can also have unevenness on the main surface, for example, it can also be embossed glass. Embossed glass can be formed by a method called roll-out method. The embossed glass obtained by this method usually has periodic unevenness along one direction of the main surface of the glass plate.
[0047] In the float glass process, molten glass is continuously supplied to a molten metal such as molten tin, and the supplied molten glass is flowed on the molten metal to be formed into a ribbon. The glass formed in this way is called a glass ribbon.
[0048] The glass ribbon is cooled as it moves downstream, and after being cooled and solidified, it is taken out from the molten metal by rollers. It is then transported to a slow cooling furnace by rollers, and after being slowly cooled, it is cut. In this way, a float glass sheet is obtained.
[0049] The thickness of the glass plate 1 is not particularly limited, but the thinner the thickness, the better for weight reduction. For example, it is preferably 0.1 to 5 mm, and more preferably 0.1 to 2.5 mm. The reason is that if the glass plate 1 is too thin, the strength will be reduced, and if it is too thick, the protected member 200 viewed through the glass member 10 may be distorted.
[0050] The glass plate 1 can generally be a flat plate or a curved plate. In particular, when the surface shape of the protected component 200 to be protected is a non-planar surface such as a curved surface, the glass plate 1 preferably has a main surface that conforms to the non-planar shape of the protected component. In this case, the glass plate 1 can be bent in a manner that allows the entire glass plate 1 to have a fixed curvature, or it can be partially bent. The main surface of the glass plate 1 can also be composed of, for example, multiple flat surfaces connected to each other by curved surfaces. The radius of curvature of the glass plate 1 can be set, for example, to be less than 5000 mm. The lower limit of the radius of curvature can be set, for example, to be greater than 10 mm, and can be even smaller in particularly locally curved areas, for example, it can be set to greater than 1 mm.
[0051] A glass plate having the following composition may also be used. In the following, unless otherwise specified, the % descriptions indicating the components of the glass plate 1 refer to mol%. In addition, in this specification, "substantially composed of" means that the total content of the listed components accounts for 99.5% by mass or more, preferably 99.9% by mass or more, and more preferably 99.95% by mass or more. "Substantially not containing" means that the content of the component is 0.1% by mass or less, preferably 0.05% by mass or less.
[0052] Examples of glass that can be used for the glass plate 1 include absorbing glass (near infrared absorbing glass) in which CuO or the like is added to fluorophosphate glass or phosphate glass, soda-lime glass, borosilicate glass, alkali-free glass, and quartz glass. In addition, "phosphate glass" also includes glass having a glass skeleton composed of SiO 2 Made of silicate phosphate glass.
[0053] The glass that can be used for the glass plate 1 is a glass composition with a high refractive index. For example, the composition is expressed as follows in terms of mol% based on oxides: 30% to 80% of TiO selected from high refractive index components. 2 、 2 O 5 , WO 3 , Nb 2 O 5 、ZrO 2 and Ln 2 O 3 (Ln is selected from at least one of Y, La, Gd, Yb and Lu); and a total content of 20% to 70% of the glass skeleton component, namely SiO 2 With B 2 O 3 ; and if it contains alkaline earth metal components (MgO, CaO, SrO, BaO), the ratio of BaO in the alkali metal components is less than 0.5.
[0054] In addition, the glass plate 1 can be obtained by molding molten glass into a plate shape by a molding method such as a so-called float glass process, a melting method, or a rolling method. In addition, after temporarily molding the molten glass into a block, the glass plate 1 can be obtained by a re-stretching method or the like. In addition, the glass plate 1 can be manufactured by methods such as reheat pressing molding or precision pressing molding. That is, a lens preform for mold pressing molding can be manufactured from optical glass, and the lens preform can be subjected to reheat pressing molding and then ground to manufacture a glass molded body, or the manufactured lens preform can be subjected to precision pressing molding after grinding to manufacture a glass molded body. In addition, the method for manufacturing the glass plate 1 is not limited to these methods.
[0055] The composition of the float glass sheet (hereinafter sometimes referred to as "SL in a narrow sense" or "SL" for short) is widely used as a glass composition suitable for manufacturing a glass sheet by a float glass process. Based on the composition of the float glass sheet, the inventors of the present invention studied a composition that maximizes T 0.05:0.05:0.05 within the composition range of soda-lime silicate glass (hereinafter sometimes referred to as "SL in a broad sense") that is considered suitable for the float glass process by those skilled in the art, specifically, within the range of mass % as follows: 2 、T 4 The properties are similar to those of SL in a narrow sense, and at the same time can improve the chemical strengthening properties of SL in a narrow sense.
[0056] SiO 2 65-80%
[0057] Al 2 O 3 0~16%
[0058] MgO 0~20%
[0059] CaO 0~20%
[0060] Na 2 O 10-20%
[0061] K 2 O 0-5%
[0062] The lithium aluminosilicate glass of the present invention preferably has the following composition (mass %):
[0063] SiO 2 63~84%
[0064] Al 2 O 3 0~8%
[0065] B 2 O 3 5-18%
[0066] (Li 2 O+Na 2 O+K 2 O) 3~14%
[0067] (MgO+CaO+SrO+BaO+ZnO)0~12%
[0068] ZrO 2 0~4%
[0069] P 2 O 5 0~2%
[0070] (Density (specific gravity): d)
[0071] By using the above composition, the density of the glass plate 1 can be reduced to 2.53 g·cm in this embodiment. -3 Below, it can be further reduced to 2.51g·cm -3 Below, can be reduced to 2.50g·cm depending on the situation -3 the following.
[0072] In float glass processes, if the density difference between glass types is large, when switching the type of glass to be manufactured, the molten glass with higher density will remain at the bottom of the melting furnace, which may cause problems in switching types. The density of soda-lime glass currently mass-produced by the float glass process is about 2.50 g·cm -3 Therefore, considering mass production by float glass process, the density of the glass plate 1 should be close to the above value, specifically 2.45 to 2.55 g·cm -3 , especially preferably 2.47 to 2.53 g·cm -3 , more preferably 2.47 to 2.50 g·cm -3 .
[0073] (Elastic modulus: E)
[0074] If chemical strengthening accompanied by ion exchange is performed, the glass substrate may sometimes be warped. In order to suppress the warping, the elastic modulus of the glass plate 1 is preferably high. According to the present invention, the elastic modulus (Young's modulus: E) of the glass plate 1 can be increased to 70 GPa or more, and further increased to 72 GPa or more.
[0075] Next, chemical strengthening of the glass plate 1 will be described.
[0076] (Chemical strengthening conditions and compressive stress layer)
[0077] The glass plate 1 containing sodium is brought into contact with a molten salt to perform an ion exchange treatment, wherein the molten salt contains monovalent cations having an ion radius larger than that of sodium ions, preferably potassium ions, and the ion exchange treatment replaces the sodium ions in the glass plate 1 with the monovalent cations, thereby enabling chemical strengthening of the glass plate 1 of the present invention. As a result, a compressive stress layer capable of imparting compressive stress to the surface can be formed.
[0078] As the molten salt, potassium nitrate is typically used. Although a mixed molten salt of potassium nitrate and sodium nitrate can also be used, the concentration of the mixed molten salt is difficult to control, so a molten salt of potassium nitrate alone is preferred.
[0079] The surface compressive stress and the depth of the compressive stress layer of the strengthened glass member can be controlled not only by the glass composition of the article but also by the molten salt temperature and treatment time in the ion exchange treatment.
[0080] The above glass plate 1 can be brought into contact with potassium nitrate molten salt to obtain a strengthened glass component having a very high surface compressive stress and a very deep depth of the compressive stress layer. Specifically, a strengthened glass component having a surface compressive stress of 700 MPa or more and a compressive stress layer depth of 20 μm or more can be obtained, and further a strengthened glass component having a compressive stress layer depth of 20 μm or more and a surface compressive stress of 750 MPa or more can be obtained.
[0081] In addition, when using a glass plate 1 having a thickness of 3 mm or more, air cooling strengthening may be used as a general strengthening method instead of chemical strengthening. Regarding strengthening treatment, strengthening treatment is generally performed on the covering member, but strengthening treatment is not necessary depending on the application or required characteristics. In addition, strengthening treatment is often performed before forming a functional film (described later), but it can also be performed after forming the functional film without hindering the functional film from exhibiting its functions.
[0082] <2. Low reflection film>
[0083] <2-1. Composition of low reflection film>
[0084] Next, refer to Figure 2 A low-reflection film is described. Figure 2 is a cross-sectional view of a low-reflection film. Figure 2 As shown, the low reflection film 2 includes hollow fine particles 21 and a binder 22. The binder 22 is mainly formed of silicon dioxide and polysilsesquioxane and is used to bind the hollow fine particles 21.
[0085] <2-1-1. Adhesive>
[0086] The content of polysilsesquioxane in the binder 22 is, for example, 30 to 70% by mass, preferably 40 to 70% by mass, and more preferably 50 to 60% by mass. The content of polysilsesquioxane in the binder 22 can be determined by, for example, a spectroscopic method such as Fourier transform infrared spectroscopy (FT-IR) and Si-NMR, a chemical method using elemental analysis, or a thermal analysis method such as thermogravimetric analysis (TG).
[0087] The silicon dioxide forming the binder 22 is formed by, for example, hydrolyzing and dehydrating condensing tetrafunctional alkoxysilane. In addition, the polysilsesquioxane forming the binder 22 is formed by, for example, hydrolyzing and dehydrating condensing trifunctional alkoxysilane. In this way, the binder 22 can be formed by, for example, a sol-gel method. As a result, the binder 22 easily has a dense structure.
[0088] The polysilsesquioxane forming the binder 22 is, for example, a polysilsesquioxane in which an alkyl group having 16 or less carbon atoms, preferably 1 to 5 carbon atoms, is bonded to a silicon atom. In this case, the binder 22 is easily dense, and the binder 22 can exert an appropriate water-repellent effect. As a result, the zinc oxide-containing composite particles 1 can more reliably have high acid resistance and have long-term stability even when in contact with water. In addition, the zinc oxide-containing composite particles 1 can more reliably be well dispersed in water. The alkyl group can be either a straight chain or a branched chain.
[0089] The polysilsesquioxane forming the adhesive 22 preferably contains at least one polysilsesquioxane selected from polymethylsilsesquioxane, polyethylsilsesquioxane and polypropylsilsesquioxane. Polymethylsilsesquioxane is a polysiloxane having a basic structural unit with one methyl group bonded to one silicon atom. Polyethylsilsesquioxane is a polysiloxane having a basic structural unit with one ethyl group bonded to one silicon atom. Polypropylsilsesquioxane is a polysiloxane having a basic structural unit with one 1-propyl group or one 2-propyl group bonded to one silicon atom. In addition, as the polysilsesquioxane, for example, methyltriethoxysilane can be used.
[0090] In addition, the adhesive 22 may also contain a cross-sectional area of 700 nm 2 The following void 23 and cross-sectional area is 1000nm 2 At least one of the plurality of cavities 23 described above. In addition, relative to the cross-sectional area of the adhesive 22 of 1 μm 2 , the cross-sectional area can be 1000nm 2 The number of the above cavities 23 is set to 10 / μm 2 the following.
[0091] <2-1-2. Hollow particles>
[0092] The hollow particles 21 are not particularly limited as long as they have a hollow structure, and have shapes such as spherical, cylindrical, or flaky. The hollow particles 21 have an average particle size (primary particle size) of, for example, 10 to 150 nm. As a result, the hollow particles 21 are easily dispersed evenly in the low-reflection film 2. The average particle size of the hollow particles 21 can be determined by, for example, observing the particle sizes of 50 or more hollow particles 21 using a transmission electron microscope (TEM) or a scanning electron microscope (SEM), and calculating the arithmetic average thereof. In addition, the particle size of each particle refers to the maximum diameter.
[0093] The hollow particles 21 preferably have an average particle size of 20 to 100 nm, more preferably 30 to 70 nm. In addition, the maximum size of the internal space in the hollow particles 21 is, for example, 5 to 100 nm, preferably 10 to 70 nm, and more preferably 20 to 50 nm. The hollow particles 21 are preferably monodisperse particles having a coefficient of variation of 0.1 or less.
[0094] The material of the hollow particles 21, for example, can be an inorganic material or an organic material if it is a material having a refractive index of 1.15 to 2.70. The material of the hollow particles 21 is preferably a material having a refractive index of 1.20 to 2.00, more preferably a material having a refractive index of 1.18 to 1.40, and more preferably a material having a refractive index of 1.20 to 1.35. From the viewpoint of being difficult to deform due to external forces, the hollow particles 21 are preferably made of an inorganic material. At this time, the hollow particles 21 are made of, for example, at least one selected from silicon dioxide, magnesium fluoride, aluminum oxide, aluminum silicate, titanium oxide, and zirconium oxide.
[0095] In order to provide an antireflection structure with high antireflection performance formed by low refractive index coating using the low reflection film 2, the hollow fine particles 21 are preferably made of silicon dioxide or magnesium fluoride. In addition, the refractive index of silicon dioxide is 1.46, and the refractive index of magnesium fluoride is 1.38.
[0096] The structure and material of the hollow particle 21 are determined so that the hollow particle 21 has a desired refractive index. For example, the material of the hollow particle 21 and the ratio of the internal space to the entire volume of the hollow particle 21 are determined so that the hollow particle 21 has a desired refractive index.
[0097] The refractive index of the hollow particles 21 can be measured by, for example, an immersion method (Becke line method). For example, when the hollow particles 21 are made of silicon dioxide, the refractive index of the hollow particles 21 can be measured according to the following procedure. (i) The dispersion medium of the dispersion liquid of the hollow particles 21 is evaporated and dried to obtain a powder. (ii) The powder obtained in (i) is mixed with various standard refractive index liquids having different refractive indices such as the A series and AA series manufactured by GARGILL. (iii) The refractive index of the standard refractive index liquid used when the mixed liquid obtained in (ii) becomes transparent is determined as the refractive index of the hollow particles 21.
[0098] The hollow microparticles 21 can be commercial products or hollow microparticles made by a prescribed method. For example, the hollow microparticles 21 can also be made by removing the core after forming a shell around the core. For example, a shell made of silicon dioxide or a shell made of magnesium fluoride is formed around a polymer core having a particle size of tens of nanometers. Afterwards, the polymer core is removed by dissolving it in a solvent or burning it, and the hollow microparticles 21 as hollow silicon dioxide particles or hollow magnesium fluoride particles can be obtained. In addition, a shell made of magnesium fluoride is formed around a core made of silicon dioxide, and then the core made of silicon dioxide is dissolved with an alkali, and the hollow microparticles 21 as hollow magnesium fluoride particles can also be obtained.
[0099] <2-1-3. Mass ratio of hollow fine particles to binder>
[0100] In the low reflection film 2 , the ratio of the mass Wh of the hollow fine particles 21 to the mass Wb of the binder 22 (Wb:Wh) is, for example, preferably 50:50 to 99:1, more preferably 75:25 to 98:2, and particularly preferably 75:25 to 95:5.
[0101] For example, if the mass ratio of the adhesive 22 is small, the hollow particles 21 may be exposed in large quantities from the low-reflection film 2 after film formation, so the refractive index is reduced and the low-reflection function is improved, but the function of bonding the hollow particles 21 is reduced, so the wear resistance may be reduced. On the other hand, if the mass ratio of the adhesive 22 is large, the function of bonding the hollow particles 21 is improved, so the wear resistance is improved, but the hollow particles 21 will be buried in the low-reflection film 2, so the refractive index is improved and the low-reflection function is likely to be reduced. From this viewpoint, it is preferred to set the mass ratio of the adhesive 22 as described above.
[0102] The thickness of the low-reflection film 2 is not particularly limited, but can be set to, for example, 50 to 100 nm, provided that the mass ratio of the hollow fine particles 21 to the binder 22 is as described above.
[0103] In addition, the low-reflection film 2 of the present invention is not limited to the one directly laminated. For example, there may be a layer of SiO between the glass plate 1 and the low-reflection film 2. 2 、TiO 2 MgO 2 The base layer is composed of the following. The base layer can be laminated by, for example, vapor deposition, sputtering, spray coating, dip coating, etc., but is not limited to these lamination methods.
[0104] <2-2. Method for producing low-reflection film>
[0105] The low reflection film 2 is, for example, a cured product obtained by curing a predetermined liquid composition (coating liquid). The liquid composition mainly contains hollow fine particles 21, silica, polysilsesquioxane, and a solvent.
[0106] The low reflection film coating liquid can be applied by various methods such as spin coating, roll coating, spray coating, etc. After coating, the low reflection film 2 is formed by heat treatment at 200° C. or higher. Therefore, the solvent may contain a solvent having a boiling point of 200° C. or higher.
[0107] As the solvent having a boiling point of 200° C. or higher, for example, glycerin, 1,3-butanediol, etc. can be used, and the coating liquid preferably contains, for example, 30 to 80% by weight. In addition to the high boiling point solvent, propylene glycol monomethyl ether (PGME), methyl ethyl ketone, toluene, methyl isobutyl ketone, etc. can also be mixed.
[0108] <3. Performance of low-reflection film>
[0109] <3-1. Optical properties of low reflection film>
[0110] In order to exert sufficient low reflection performance, the refractive index of the low reflection film 2 is preferably less than 1.20, and more preferably less than 1.16. The voids in the adhesive 22 help to achieve such a low refractive index. In addition, the refractive index is measured using a spectrophotometer (manufactured by Hitachi High-Technologies Corporation, product name: U-4000). The reflectivity is measured in each of the embodiments and comparative examples described below, and the refractive index of the low refractive index film of each embodiment and comparative example is determined by reflectance spectroscopy.
[0111] <3-2. Abrasion resistance of low reflection film>
[0112] As the wear resistance test, the cotton swab rubbing method shown below was used. Figure 3 As shown, a rod-shaped fixture with a cotton swab installed at the front end is set vertically relative to the low-reflection film. Then, the fixture is pressed against the low-reflection film with a specified load and moved back and forth a specified number of times. Then, the dynamic friction coefficient is measured and the surface properties of the low-reflection film are observed. In addition, the cotton swab used is an industrial cotton swab made by Japan Cotton Swab (P3D-100).
[0113] <3-2-1. Cotton swab wiping method; observation of peeling after wiping in "single abrasion test">
[0114] In the cotton swab wiping method, a cotton swab was pressed against the low-reflection film with a fixed load, i.e., no weight, 1g, 6g, 20g, 50g, 100g, 150g, 200g, 300g, and scraped once at a distance of 3cm. At this time, the case where the low-reflection film was not peeled off was set as OK. In addition, when the cotton swab was pressed against the low-reflection film with the above load and scraped once at a distance of 3cm, when the low-reflection film peeled off, a load one level lighter than the load when the peeling occurred was measured, and this load was set as the "wear resistance load".
[0115] <3-2-2. Cotton swab wiping method; Changes in dynamic friction coefficient before and after wiping>
[0116] In addition, in the cotton swab wiping method, when the cotton swab is pressed against the low-reflection film with a load of 100 g and moved back and forth 10 times at a distance of 3 cm, the change in the dynamic friction coefficient during the first round trip and the dynamic friction coefficient during the tenth round trip is 0.2 or less, preferably 0.1 or less. In addition, the rate of change of the dynamic friction coefficient (the above change / dynamic friction coefficient during the first round trip) is preferably 40% or less.
[0117] <4. Features>
[0118] The low-reflection member 100 of this embodiment can achieve the following effects.
[0119] (1) Since the low-reflection film 2 contains the hollow fine particles 21, a low refractive index can be achieved, thereby improving the low-reflection performance.
[0120] (2) Since the ratio (Wb:Wh) of the mass Wh of the hollow fine particles 21 and the mass Wb of the binder 22 is adjusted as described above, both low reflection performance and abrasion resistance performance can be achieved.
[0121] (3) Since the coating liquid contains a high-boiling-point solvent, the high-boiling-point solvent evaporates after the sol-gel polycondensation reaction when forming the low-reflection film 2. Therefore, the wear resistance of the low-reflection film 2 is improved. In addition, the above-mentioned voids are formed by the evaporation of the solvent after the sol-gel polycondensation reaction.
[0122] Example
[0123] The following are examples of the present invention, but the present invention is not limited to the following examples.
[0124] (1) Preparation of Examples and Comparative Examples
[0125] The low-reflection members of Example and Comparative Examples 1 and 2 were formed by laminating a low-reflection film on a glass plate (D263 manufactured by SCHOTT) having a thickness of 0.21 mm and a size of 76 mm×76 mm.
[0126] A coating liquid having the composition shown in Table 1 (unit: mass %) was prepared so that the total amount of the coating liquid was 1.0 g.
[0127] [Table 1]
[0128]
[0129] Silica (binder): tetraethyl orthosilicate (manufactured by Tama Chemicals Co., Ltd.)
[0130] Methyltriethoxysilane (MTES) (binder): KBE-13 (manufactured by Shin-Etsu Silicone Co., Ltd.)
[0131] Silica hollow fine particles: THRULYA (manufactured by JGC C&C Ltd.)
[0132] Leveling agent: KP341 (manufactured by Shin-Etsu Silicone Co., Ltd.)
[0133] PGME (solvent): 1-methoxy-2-propanol (manufactured by Tokyo Chemical Industry Co., Ltd.)
[0134] Glycerin (solvent): Glycerin (manufactured by Hayashi Pure Chemical Ind., Ltd.)
[0135] Next, the coating liquid was flow-coated on a glass plate to a thickness of about 100 nm, dried naturally for 10 minutes, and then heated in an oven set at 200° C. for 10 minutes to form a low-reflection film. In this manner, the low-reflection members of Examples 1 and 2 and the comparative example were completed.
[0136] (2) Evaluation
[0137] The cross sections of the low-reflection films of Examples 1 and 2 and the comparative example were photographed using a SEM. Figure 4 For Example 1, Figure 5 For Example 2, Figure 6 In Examples 1 and 2, the gaps between the hollow particles were filled with the adhesive, and it was clearly known that the hollow particles were sufficiently bonded. On the other hand, in the comparative example, gaps between the hollow particles were seen in many places, and it was known that the hollow particles were not sufficiently bonded by the adhesive.
[0138] Furthermore, the following tests were conducted on the low-reflection members of Examples 1 and 2 and the comparative example.
[0139] (2-1) Optical properties
[0140] The refractive index was measured by the above-mentioned method.
[0141] (2-2) Wear resistance test
[0142] As a wear test, the above-mentioned cotton swab rubbing method was used, and the changes in the wear load and the dynamic friction coefficient were measured. The results are as follows.
[0143] [Table 2]
[0144]
[0145] As shown in Table 1, although Example 1 contains glycerin in the solvent, the composition of the solid components of Examples 1 and 2 is the same. As shown in Table 2, Example 1 contains glycerin in the solvent, so it can be processed at high temperature, and the refractive index is lower than that of Example 2. However, the wear resistance load becomes lower than that of Example 2. On the other hand, since the hollow particles of the comparative example are not filled, the refractive index is low, but the wear resistance is also low, and the low-reflection film is still peeled off even under a load of 1g (so the result is 0g). The wear resistance loads of Examples 1 and 2 are both above 100g. That is, when a cotton swab is pressed against the low-reflection film with a load of more than 100g, and the low-reflection film is scraped once at a distance of 3cm, it will not peel off. Therefore, it can be seen that it has high wear resistance.
[0146] The variation of the dynamic friction coefficient is shown in Figure 7 .like Figure 7 As shown, in Example 2, even if the cotton swab is moved back and forth 10 times, the dynamic friction coefficient remains almost unchanged. On the other hand, in Example 1 and the comparative example, as the number of times the cotton swab is moved back and forth increases, the dynamic friction coefficient increases, but in Example 1, when the number of times exceeds 5 times, the increase in the dynamic friction coefficient decreases, and the change after 10 times is less than 0.20. The dynamic friction coefficient of the comparative example continues to increase, and the change after 10 times is 0.28. As the dynamic friction coefficient increases, there is a fear that scratches will occur on the low-reflection film and it will peel off. In particular, if the change in the dynamic friction coefficient exceeds 0.20, peeling of the low-reflection film is confirmed in the following manner.
[0147] Figure 8 Enlarged views of the low-reflection film before and after abrasion in a comparative example when measuring the change in dynamic friction coefficient. Figure 8 The white area B shown indicates that even if there are slight scratches, the low-reflection film still remains. On the other hand, the dark area A reflects the glass plate instead of the low-reflection film. That is, it means that the low-reflection film is peeled off from the glass plate and no residue remains. In addition, although the illustration is omitted, the low-reflection film remains in Examples 1 and 2. Therefore, it can be seen that the change in the dynamic friction coefficient is preferably less than 0.20.
[0148] Explanation of symbols:
[0149] 1: Glass Plate
[0150] 2: Low reflection film
[0151] 21: Hollow particles
[0152] 22: Adhesive
[0153] 100: Low reflective components
[0154] 200: Protected components.
Claims
1. A low-reflection component, characterized in that: have: A glass plate having a first surface and a second surface, and a low reflection film formed on the first surface and having a refractive index lower than that of the glass plate, The low-reflection film comprises hollow fine particles and a binder. Even after a cotton swab was pressed against the low-reflection film with a load of 10 g or more and scraped once at a distance of 3 cm, the low-reflection film was not peeled off.
2. A low-reflection component, characterized in that: have: A glass plate having a first surface and a second surface, and a low reflection film formed on the first surface and having a refractive index lower than that of the glass plate, The low-reflection film comprises hollow fine particles and a binder. When the woven fabric was pressed against the low-reflection film with a load of 100 g and moved back and forth 10 times at a distance of 3 cm, the change in the dynamic friction coefficient between the first back and forth movement and the dynamic friction coefficient between the tenth back and forth movement was 0.2 or less.
3. The low-reflection member according to claim 1 or 2, characterized in that: In the low-reflection film, a mass ratio of the hollow fine particles to the binder is 50:50 to 99:
1.
4. The low-reflection member according to claim 1 or 2, characterized in that: In the low-reflection film, a mass ratio of the hollow fine particles to the binder is 70:30 to 95:
5.
5. The low-reflection member according to claim 1 or 2, characterized in that: The binder comprises silica and polysilsesquioxane.
6. The low-reflection member according to claim 1 or 2, characterized in that: The refractive index is less than 1.
20.
7. The low-reflection member according to claim 1 or 2, characterized in that: The refractive index is 1.18 or less.
8. The low-reflection member according to claim 1 or 2, characterized in that: There are gaps between the hollow particles, and the gaps have a diameter of 1000 nm. 2 The cross-sectional area above.
9. The low-reflection member according to claim 1 or 2, characterized in that: The adhesive also has pores having a diameter of 700 nm. 2 The following cross-sectional area.
10. The low-reflection member according to claim 1 or 2, characterized in that: Even after a cotton swab was pressed against the low-reflection film with a load of 50 g or more and scraped once at a distance of 3 cm, the low-reflection film was not peeled off.
11. The low-reflection member according to claim 1 or 2, characterized in that: Even after a cotton swab was pressed against the low-reflection film with a load of 100 g or more and scraped once at a distance of 3 cm, the low-reflection film was not peeled off.
12. The low-reflection member according to claim 1 or 2, characterized in that: The pencil hardness is higher than 2B.
13. The low-reflection member according to claim 1 or 2, characterized in that: It can be used as an optical component that can be stored inside a frame.
14. The low-reflection member according to claim 13, wherein: The optical component is a lens.
15. The low-reflection member according to claim 13, wherein: The optical component is a covering member, The low reflection film is arranged to face the inside of the frame.
16. A coating liquid for a low-reflection film which can be applied on a glass plate, characterized in that: Contains: hollow particles, a binder and a solvent with a boiling point above 200°C.
Citation Information
Patent Citations
Substrate with antiglare film
JP2020118992A